Multi-disciplinary 3-D reservoir characterization and flow simulation of Aptian/Albian silicate sandstone reservoirs in Bredasdorp Basin, offshore South Africa - Onaneye, Alfred Omololu (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc)--Stellenbosch University, 2014.